A Comparative Study of the French & Italian Translations of Anne Michaels’ Fugitive Pieces - Gordon, W. (TTR)

(untitled) (Association canadienne de traductologie, 2002)
AbstractW. Terrence Gordon examines the notion of translation problems by comparing the French and Italian versions of Michaels’ work. He begins by examining the translation of geological terms which, although they cause no translation problems on a strictly scientific level, are a cause of divergence in the French and Italian versions because they express metaphorically a main theme of the novel: memory and the modifying effect that the past has on the present. Gordon also examines the strategy of each translator with regards to word play, and in particular homonyms, anagrams and palindromes, which are rendered anywhere from a strictly didactic translation to a translation based on various linguistic resources and creative expression. Gordon reminds us that we are invited to study the stylistique interne of English-French and English-Italian through the two translations.